The Holocaust in selected European feature films, 2010-2013 - Torsten, Schaar; Ogasa, Nicole (Peter Lang Publishing, 2015)
The production of Holocaust-theme-based dramas has been an essential part of European filmmaking since the end of World War II. One third of the World War II narratives made in Europe between 2010 and 2013 shed light on that singular crime of the twentieth century from the unique perspective of each country. Multi-award-winning films preserve memory and raise awareness by portraying newly discovered or “forgotten” true stories of loss and survival, of the pervasive horror, of courage and cowardice, of selfless acts of kindness, compassion and of indifference in France, The Netherlands, Poland, and Ukraine/Soviet Union and in Bulgaria controlled Macedonia. Several inspiring films pay tribute to the fate of Jewish children and to the courage of Jew helpers and their dramatic circumstances. Filmmakers from France and Poland have also touched on thus far untold national traumata and taboos, on sensitive issues and darker chapters in their countries’ history depicting acts of active involvement in the Holocaust. Since the cinematic representation of death inside the gas chambers is an accepted taboo in European filmmaking, the Holocaust is shown in scenes of the persecution, isolation and round-up of the Jews; and by the use of Holocaust iconography and symbols. Several films however depict gruesome scenes in which Jewish men, women and children are shot, beaten to death or burned alive.